2016
DOI: 10.1002/evan.21484
|View full text |Cite
|
Sign up to set email alerts
|

Reading the landscape: Legible environments and hominin dispersals

Abstract: Wayfinding, or the ability to plan and navigate a course over the landscape, is a subject of investigation in geography, neurophysiology, psychology, urban planning, and landscape design. With the prevalence of GPS-assisted navigation systems, or "wayfinders," computer scientists are also increasingly interested in understanding how people plan their movements and guide others. However, the importance of wayfinding as a process that regulates human mobility has only recently been incorporated into archeologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…These two regions represent both geographical and chronological discontinuity with the region consisting of East Africa, the Nile Valley, the Negev desert and Arabia. For a group of hunter-gatherers to disperse across geographical regions the landscape must be legible to them (Guiducci & Burke 2016). Water ways have been shown to facilitate movement of populations (Breeze et al 2016;Scerri et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These two regions represent both geographical and chronological discontinuity with the region consisting of East Africa, the Nile Valley, the Negev desert and Arabia. For a group of hunter-gatherers to disperse across geographical regions the landscape must be legible to them (Guiducci & Burke 2016). Water ways have been shown to facilitate movement of populations (Breeze et al 2016;Scerri et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The results of studies have shown that one of the visual attributes of legibility in a landscape is the presence of salient elements. These elements are effective in human perceptions of a landscape and are easily memorized [36].…”
Section: Distinctive Elementsmentioning
confidence: 99%
“…The vast purview of intricate, multitemporal intercalations of Pleistocene climate and environmental change with peopling and re-peopling processes and hominin population expansions and retractions on both local and global scales also provides the hitherto neglected opportunity to critically investigate the sociocultural appropriation of newly encountered constellations of climate, landscape, and environment. Archeological research on landscape learning (Rockman, 2009) and environmental legibility (Guiducci & Burke, 2016) is of key importance here. This work yields novel insights into those episodes where past humans expanded into unfamiliar territory or where their ambient territories became unfamiliar due to climate change (e.g., Hiscock, 2014) and paleoarcheologists are in a chief position to examine in detail how humans in the long-run-under varying social and material conditions-learned, or failed to learn, previously unknown local and regional climate conditions.…”
Section: Pleistocene Archeology Catalytic Climates and The Dark MImentioning
confidence: 99%